Los factores desencadenantes y su relación en las crisis asmáticas en personas de la ciudadela Cristo del Consuelo 2 del cantón Babahoyo en el primer semestre del 2017 - Albán Aguilar, Billy Joe (2017)
The research that has been carried out in the Ciudadela Cristo del Consuelo 2, looks for information that allows to know which are the main factors that trigger an asthmatic crisis, due to the increase to the exposure to homemade allergens, when there is manifested the needs that allow to apply A program of talks related to the care, prevention and improvement of the lifestyle of the residents in the Cristo del Consuelo Citadel 2 of Babahoyo. Provide knowledge to the residents with asthma of the Citadel Cristo del Consuelo 2 about the main risk factors that produce an asthmatic crisis, managing to provide the city with residents who can be in an environment free of contaminants that can cause an asthma crisis and Improve the lifestyle of the residents of this citadel of life. To stimulate the residents of the Citadel Cristo del Consuelo 2 by means of talks aimed at the care of people with asthmatic crisis, in order to avoid frequent episodes of asthmatic crisis and thus to protect the health of the residents of the citadel Cristo del Consuelo 2.